Host MicroRNA-217 Promotes White Spot Syndrome Virus Infection by Targeting Tube in the Chinese Mitten Crab (Eriocheir sinensis) - Huang, Ying; Han, Keke; Wang, Wen; Ren, Qian (Frontiers in Cellular and Infection Microbiology, 2017)
MicroRNAs (miRNAs), a group of small molecule non-encoding RNAs, are key posttranscriptional regulators of gene expression that are implicated in many biological processes. In the current study, miR-217 from Eriocheir sinensis was selected for studying its roles during host–virus interaction. Overexpression or silencing of miR-217 led to considerable effects on white spot syndrome virus (WSSV) replication, implying that miR-217 played a positive role in WSSV infection. In insect High Five cells, miR-217 significantly inhibited Tube gene expression by binding to the 3’-untranslated region of the Tube. Overexpression of miR-217 in crab led to downregulation of tube expression. Knockdown of Tube in vivo led to significant enhancement of WSSV infection and inhibited the expression of five antimicrobial peptide (AMP) genes (Anti-lipopolysaccharide factor ALF1, ALF2, ALF3; Crustin Crus1, Crus2) in WSSV-challenged crabs. Overexpression of miR-217 also led to downregulation of these AMP genes in WSSV-challenged crabs. Our results showed that host miRNA played positive roles in virus infection by regulation of host tube gene, which is the key component of Toll signaling pathway.